Federated Learning: The Pioneering Distributed Machine Learning and Privacy-Preserving Data Technology. - Treleaven, Philip; Smietanka, Malgorzata; Pithadia, Hirsh (Computer (00189162), 2022)
Federated learning (pioneered by Google) is a new class of machine learning models trained on distributed data sets, and equally important, a key privacy-preserving data technology. The contribution of this article is to place it in perspective to other data science technologies.